Active drag device for resistance training in the pool - Whiticker, R.; Lee, J.; James, D.; Mirnajafizadeh, A.; Simpson, B. (Journal of Fitness Research, 2016)
Swimming resistance gear is aimed at conditioning competitive swimmers. As part of a training program,competitive swimmers are typically cycled through training strokes with elements of additional resistance to build strength, resilience and simulate fatigue.The challenge is provide variable resistance levels within a single session,dependent on specific needs and training objectives. In this paper varied concepts were created that make use of remote wireless control systems and were compared in a criteria weighted Pugh Matrix. The winning concept, a tethered cone device, scored highly for its simplicity and cost. Although the product is initially aimed at elite athletes, it is likely that the design will have utility in recreational swimming and rehabilitation.